DNA bending by retinoid X receptor-containing retinoid and thyroid hormone receptor complexes. - Lu, X P (1993)
Retinoid X receptors (RXR) have been identified as common subunits in the regulation of multiple hormonal signaling pathways. Using circular permutation and phasing analysis of specific response elements, we present evidence that RXR-retinoic acid receptor and RXR-thyroid hormone receptor heterodimer or RXR-RXR homodimer complexes induce directed DNA bends when bound to their cognate response elements. The extent of DNA bending induced by the RXR alpha-containing complexes varied and depended on the structure of the DNA-binding sites and the RXR partners. The overall bending orientation for RXR-containing complexes is directed toward the major groove of the DNA helix at the center of hormone response elements. Our observation implicates DNA bending as a possible mechanism underlying transcriptional regulation of distinct retinoid and thyroid hormone responsive genes.